FAKTOR PENYEBAB KETIDAKLENGKAPAN IMUNISASI DASAR - Vyola Chania Arefti; Mukhlisiana Ahmad; Lia Indria Sari; Eny Sendra (Ensiklopedia Research and Community Service Review, 2026)
Basic immunization is a preventive measure in the form of vaccination for children that aims to boost immunity so that various infectious diseases can be prevented. Based on document searches, the Lelogama Community Health Center is one of the community health centers with basic immunization coverage below the standard. The purpose of this study was to determine the factors causing incomplete basic immunization. The research design used in this study was cross-sectional. The research was conducted in the working area of the Lelogama Community Health Center. The research was conducted in July 2025. The population consisted of all mothers who had babies aged 9-24 months. The sample consisted of 60 people. The sampling technique used was purposive sampling. The research instrument used a research questionnaire. Data analysis was performed using univariate and bivariate analysis. The results showed a relationship between spousal support (p value: 0.000) and access to health services (p value: 0.025) with incomplete basic immunization. It is recommended that health center staff provide information related to immunization, not only to mothers but also to fathers, and provide training and guidance to cadres so that they are able to educate and convey information to parents regarding immunization, enabling cadres to independently provide understanding to parents. Keywords: Children, Spousal Support, Immunization.